Wood and bark lignin contents of trees from deciduous forests of eastern India. (9th September 2021) - Erickson, Richard; Deb, Debal; Roy, Priyabrata
Abstract: Lignin is a polyphenolic compound found in plant tissues, especially wood and bark. The lignin content determines the quality of wood biochar in agroecological uses, and is used in the production of synthetic resins and adhesives. Despite its importance in plant physiology and its agricultural and industrial utility, there exists a wide gap of knowledge of lignin contents of tropical hardwood trees of South Asia, except for a few species. We present here the first estimation of lignin content in wood and bark of 48 species from tropical deciduous forests of India. We show that some species are characterized by greater wood lignin (WL) compared with bark lignin (BL) content, contrary to the generalization held for hardwood trees, and suggest a plausible correspondence between the WL to BL ratio and timber quality.